Effect of Benzoic Acid, Myristic Acid, and Aspergillus Niger on the AME and N Retention in Grow-Finishing Pigs - Diego A. Lopez; Mason J. Engnell; Allison K. Blomme; Carter Minson; W. Garrett Friesen; Victoria C. Wilson; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2024)
An experiment was conducted to determine the effect of benzoic acid, myristic acid, and Aspergillus niger on the digestibility of DM and GE, and the concentration of DE and ME in diets fed to growing pigs. A total of 10 barrows (DNA 200 × 400, DNA; initially 75.2 ± 2.27 lb.) were allotted to a replicated 5 × 5 Latin square design with five treatments and five periods for a total of 10 replicate pigs per treatment. Pigs were individually housed in metabolic crates equipped with a feeder, drinker, and a wire mesh floor. Pigs were fed dietary treatments for a 5-day adaptation period followed by a 5-day collection period. During collection, a screen and a urine pan were installed below the floor of the crate to allow for the total and separate collection of feces and urine. A basal corn-soybean meal, wheat middlings and DDGS-based diet was formulated as a negative control and a corn soybean meal-based diet was formulated as positive control. Three additional diets were formulated by adding one source of benzoic acid, myristic acid, or Aspergillus niger to the negative control. Therefore, a total of five diets were formulated. The positive control diet had the greatest (P < 0.05) ATTD of GE and DM, ME and DE compared to the negative control diet with or without feed additives. There was no evidence of difference between ATTD of DM and GE between the negative control diet and the negative control diets with either benzoic acid, myristic acid, or Aspergillus niger. However, the negative control diet containing myristic acid had increased (P < 0.05) DE concentration compared to the negative control. There was a tendency for the negative control diets containing benzoic acid and Aspergillus niger to have increased (P < 0.15) concentration of DE compared to the negative control diet without feed additives. Similarly, there was a tendency of increased (P < 0.15) concentration of ME in diets containing added myristic acid and benzoic acid compared to the negative control diet. There was no evidence of difference (P > 0.15) in ME concentration between the negative control diet with and without Aspergillus niger. The positive control diet had the greatest (P < 0.05) N retention and N digestibility as percentage of intake compared to all negative control treatments. However, there was no evidence of differences between the negative control diet and the negative control treatments containing the feed additives. This data suggests that the inclusion of myristic acid and benzoic acid has the potential to increase the concentration of ME in diets with high fiber concentrations without impacting N retention.
Keywords: feed additives; digestibility; nitrogen balance; growing pig